Kualitas sumberdaya manusia dan sifat kewirausahaan pelaku industri kreatif usaha mikro kecil dan menengah di Kota Jambi - Junaidi Junaidi (Jurnal Paradigma Ekonomika, 2017)
This study aims to analyze: 1) the quality of human resources in the creative industries of MSMEs in Jambi City; 2) entrepreneurial nature of MSMEs creative industry entrepreneurs in Jambi City. The data used is sourced from a sample survey limited to the MSMEs creative industry in Jambi City. The analysis was carried out in a qualitative and quantitative descriptive manner. The results of the study found that: 1) The age of entrepreneurs and creative industry workers MSMEs in Jambi City was relatively young and in the productive age group. Creative industry entrepreneurs are more male-dominated but for workers who are relatively balanced between men and women. In terms of formal education it is also relatively good, but in terms of informal education such as participation in training / courses / internships are still relatively low; 2) Overall, the entrepreneurial nature of MSMEs creative industry entrepreneurs in Jambi City is categorized as good. There are five entrepreneurial traits with excellent categories, namely the nature of risk taking, the nature of hard work, innovative nature, prestige and instrumental nature. Two other traits are included in the good category, namely independence and the flexibility of socializing.